PENCEGAHAN STUNTING MELALUI PROGRAM PMT INOVATIF BERBASIS OLAHAN DAUN KELOR DI DESA GUMELAR - Saputri, Alisah Marselia; Rizal, Mohammad Saiful; Sayuti, Muhammad Indra; Vidiansyah, Mohammad Rifki; Luthfiyah, Lenny (PAPUMA: Journal of Community Services, 2025)
This community service program was implemented in Gumelar Village, Balung District, Jember Regency, to increase community knowledge of stunting prevention through the innovation of PMT (Supplementary Feeding) based on local food processing from Moringa leaves. The program was implemented by 100 students participating in a collaborative community service program (Kuliah Kerja Nyata – KKN). The program implementation method used the Participatory Rural Appraisal (PRA) approach across three stages: planning, implementation, and evaluation. Activities included community outreach of stunting prevention with balanced nutrition, interactive discussions, and demonstrations on how to make the innovative product "Morice" (moringa leaf ice cream). A total of 31 mothers' health cadres and 9 fathers participated in this activity. The implementation results indicated increased knowledge and awareness of children's nutrition, as reflected in their enthusiasm during the discussion and active involvement in the product demonstration. The innovation of moringa leaf ice cream was able to attract public attention as a healthy food alternative that children like while contributing to stunting prevention efforts. Thus, the collaboration between students, health workers, and Posyandu cadres has been proven to have a positive impact on increasing public nutrition awareness and has the potential to reduce stunting prevalence sustainably. It is recommended that similar programs be replicated in other villages and accompanied by long-term monitoring to ensure sustainable improvements in children's nutritional status.